SISTEM INFORMASI KANTOR CAMAT VII KOTO BERBASIS WEB: Service, Community, Sub-District Office, Information System, DFD - Suana, Irma; Susanti, Lilis (FORTECH (Journal of Information Technology), 2023)
Service is the provision (serving) of the needs of individuals or communities who have an interest in the organization in accordance with the basic rules and procedures specified. Good service will ultimately be able to provide satisfaction to the community. The public can directly assess the performance based on the services received. One of the problems that need attention at the Koto VII Sub-District Head Office is Community Service, which is currently still using the manual method of recording through the Service agenda book. This method will make the working method ineffective because one of the obstacles faced is when Community Service can extend the time long enough because it is still manual. This system is designed using DFD (Data Flow Diagram). The sources of research data are secondary data obtained from studies of several journals, articles, government regulations, company data, internet, and others. Which is considered relevant to the research topic. With the system application that was built, it can help, simplify, and speed up the process of Community Service to the community being more well-documented and processing the required data faster.